2021
DOI: 10.3390/catal11080908
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Iron-Based Fischer—Tropsch Catalyst with High Attrition Resistance and Stability for Industrial Application

Abstract: In order to develop an iron-based catalyst with high attrition resistance and stability for Fischer–Tropsch synthesis (FTS), a series of experiments were carried out to investigate the effects of SiO2 and its hydroxyl content and a boron promoter on the attrition resistance and catalytic behavior of spray-dried precipitated Fe/Cu/K/SiO2 catalysts. The catalysts were characterized by means of N2 physisorption, nuclear magnetic resonance (NMR), X-ray diffraction (XRD), Raman spectrum, X-ray photoelectron spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…SiO 2 has been considered as a proper structural promoter for iron-based catalysts [4]. The formula 100Fe/5Cu/4.2K/25SiO 2 from Ruhrchemie A. G. in Germany [14] was one of the classical recipes, which acts as the basic formula of precipitated iron-based FTS catalysts, has been widely used as a benchmark for basic research and industrial catalyst development [15][16][17][18]. In the research works related to SiO 2 -incorporation effects, some works have indicated that its promotion of the attrition property, FTS activity/stability and selectivity/hydrocarbon productivity of Fe catalyst seemed to some extent to exhibit contrary correlation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…SiO 2 has been considered as a proper structural promoter for iron-based catalysts [4]. The formula 100Fe/5Cu/4.2K/25SiO 2 from Ruhrchemie A. G. in Germany [14] was one of the classical recipes, which acts as the basic formula of precipitated iron-based FTS catalysts, has been widely used as a benchmark for basic research and industrial catalyst development [15][16][17][18]. In the research works related to SiO 2 -incorporation effects, some works have indicated that its promotion of the attrition property, FTS activity/stability and selectivity/hydrocarbon productivity of Fe catalyst seemed to some extent to exhibit contrary correlation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As of now, FTS has attracted renewed attention as a well-known and long-established commercial technical route to produce a wide range of synthetic paraffins and olefins from syngas comprising primarily H 2 and CO, derived from non-petroleum carbon sources, such as coal, biomass and natural gas [1][2][3][4]. In particular, for coal-based FTS processes with low H 2 /CO ratio syngas, iron-based catalysts are preferentially applied in industrial implementation, depending largely on abundant reserves, low price, adequate catalytic performance for H 2 -poor syngas and impressive selectivity for α-olefin production [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to have an optimized catalyst to make the overall FT application economical for the practitioner by ensuring high production of the desired hydrocarbons [3,10,16,20,25]. Catalytic performance is defined as a function of its activity, selectivity, and stability [9,16,19,20,[26][27][28][29][30][31]. These principles are also applicable to iron ore catalysts used in FT, which will be scrutinized to improve the current research on this type of iron catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that most of the research work carried out on the use of iron ore as a catalyst in FTS did not give significant attention to its stability. Apart from looking at the activity and selectivity of the iron ore as a catalyst in FTS, its stability is a very crucial aspect for the development of a practical reaction system [1,3,19,24,25,27,30,32,33]. A catalyst's stability can be defined as a function of the chemical and physical aspects [18,24,27,29,34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation